Gambaran Pengetahuan Ibu Tentang Stunting Pada Balita Di Klinik Pratama Vina Kecamatan Medan Baru Tahun 2023: Description of Mother’s Knowledge About Stunting in Toddlers at the Vina Primary Clinic, Medan Baru District in 2023 - Mardiati Barus; Vina Yolanda Sigalingging; Jeslian Crisyonni Zalukhu (Jurnal Midwifery, 2024)
Introduction Stunting is a picture of malnutrition in toddlers that lasts for a long time where the main factor causing stunting is the mother’s knowledge. With good knowledge, mothers can provide the right parenting style so as to prevent stunting. This study aims to describe the mother’s knowledge about stunting in toddlers at Pratama Vina ClinicMedan Baru District 2023. dealing with dysmenorrhea at SMA Negeri 12 Medan 2023. Method The research method used is a descriptive research design. The population in this study are mothers who have toddlers at Pratama Vina Clinic Medan Baru District in January 2023 with 116 total of populations. Determining the sample size using the Slovin formula obtains results of 90 respondents. Sampling technique using purposive sampling. Results show that of the 90 respondents, the majority of respondents have sufficient knowledge of 67 people (74.4%), good knowledge of 23 people (25.6%), and bad knowledge of 0 people (0%). Conclusion It is hoped that research sites will provide information to mothers through counseling and health education regarding stunting in toddlers when carrying out posyandu activities